Consumer Protection of SPHP Brand Rice in a Legal Political Perspective - Donius Ndruru; Agusmidah (Journal of Law Perspectives Review, 2026)
This study aims to analyse consumer protection against the adulteration of Stabilization of Food Supply and Price (SPHP) rice in Indonesia and to evaluate legal policy weaknesses in order to formulate responsive regulatory reforms that balance business and consumer interests. The research applies a normative legal method using Roscoe Pound's theory of law as a tool of social engineering. Primary legal materials include Law No. 8 of 1999 on Consumer Protection, Law No. 18 of 2012 on Food, and the 1945 Constitution, supported by secondary sources from legal literature and relevant cases. The results show that SPHP rice adulteration violates Article 8 of the Consumer Protection Law concerning product standards and triggers strict liability under Articles 19–23 for business actors. Weak supervision, regulatory gaps, and persistent non-compliance remain major obstacles, indicating limited effectiveness of current enforcement mechanisms in ensuring food safety. The study concludes that responsive legal policy reconstruction is necessary through stricter distribution supervision, stronger sanctions, optimisation of local government roles, and the integration of supply-chain tracking technology to enhance regulatory harmonisation and substantive consumer protection within Indonesia's food security framework.